ANALYSIS OF TRENDS IN THE AVAILABILITY OF INDICATOR DRUGS AND VACCINES IN PUBLIC HEALTH CENTER FOR 2016-2017 - Wicaksono, Aji; Siregar, Kemal Nazarudin (Journal of Indonesian Health Policy and Administration, 2019)
The health development strategies for 2015-2019 is about improving the availability, affordability, equity and quality of pharmaceuticals and medical devices. Since the enactment of national health insurance (JKN) on January 1, 2014, the availability of drug at the public health center become a very important aspect in primary health care services. Drug logistics management is an important aspect that influences accessibility to health services including the availability of essential drugs and vaccines. The aim of this study is to explore the trend of availability indicator drugs and vaccines in public health center for the period of 2016-2017 and drug logistics management factors that can affect the availability. The study was conducted using secondary data analysis. Data were obtained from data on the availability of indicator drugs and vaccines in public health center for the period of 2016-2017. This research is a quantitative study with an analytical observational approach. The Vector Auto Regression(VAR) conducted provides forecasting trends in indicator drugs and vaccines in public health center close to 80%. The 80% figure shows appropriate availability, but there are a number of things that need special attention including planning, procurement, pharmaceutical competency, financing, and management information systems.